You are correct, unless your teacher wants it as a fraction. You should always write it as a fraction, and factor the numerator and denominator completely to make sure it can not be simplified. that is what I did to make sure you were correct.
[2x^2(x-2)-4x]/(x-2)
[2x^3-4x^2-4x]/(x-2)
2x(x^2-2x-2)/(x-2)
Since x^2-2x-2 cannot be factored, there is no common factor for you to cancel and the fraction cannot be simplified further.
2006-09-29 04:33:50
·
answer #1
·
answered by mom 7
·
0⤊
0⤋
4X/X=4.
Thus the expression becomes 2X^2-4-2 or 2X^2-6
Divide by 2 and the expression becomes X^2-3
2006-09-29 03:20:30
·
answer #2
·
answered by Mendelson 2
·
0⤊
0⤋
The expression is ambiguous. If you mean 2x^2 - (4x/x) - 2, then it can be simplified to 2x^2 - 4 - 2, which is simplified to 2x^2 -6.
If, however, you mean 2x^2 - ( 4x / (x-2) ), it can't be simplified.
2006-09-29 03:22:14
·
answer #3
·
answered by tevansmd 2
·
0⤊
0⤋
2x^2-4X/X -2
= 2X^2 -4 -2 ( as 4X/X = 4)
= 2X^2 -6
kindly note how () makes a difference
but if you mean (2X^2-4X)/(X-2) Then () is necessary
numerator = 2x(x-2)
So result = 2x(x-2)/(x-2) = 2x
2006-09-29 03:14:33
·
answer #4
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
8d - (-7c - second) = 8d + 7c + second = 7c + 10d to study, Subsitute d = 2, c = 3 into 8d - (-7c - second) 8 x 2 - (-7 x 3 - 2 x 2) = 16 - (-21 - 4) = 16 - (-25) = 16 + 25 = 40-one to study, Subsitute d = 2, c = 3 into 7c + 10d 7 x 3 + 10 x 2 = 21 + 20 = 40-one therefore the equation is ideal. favor this helps.
2016-12-06 09:15:51
·
answer #5
·
answered by ? 4
·
0⤊
0⤋
factor out 2x from numerator
2x ( x - (1/(x-2) )
2006-09-29 03:32:34
·
answer #6
·
answered by Brian D 5
·
0⤊
0⤋
Ignore the first answer. You were correct....your expression is simplified.
2006-09-29 03:14:55
·
answer #7
·
answered by Jimmy Crack Corn 2
·
0⤊
0⤋
(2x^2-4x)/(x-2)=
(2x*(x-2))/(x-2)=
2x
2006-09-29 03:25:47
·
answer #8
·
answered by Mamad 3
·
0⤊
0⤋
cant be reduced further...
2006-09-29 03:12:27
·
answer #9
·
answered by ashwin_hariharan 3
·
0⤊
0⤋
take common denominator
2x^2(x-2)-4x
---------------
x-2
2x^3-4x^2-4x
-----------------
....x-2
2x(x^2-2x-2)
----------------
...x-2
2006-09-29 03:09:57
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋